ASSOCIATION BETWEEN HEALTH LITERACY AND PREVENTING AND CONTROLLING BEHAVIOR FOR COVID-19 PREVENTION AND CONTROL AMONG VILLAGE HEALTH VOLUNTEERS IN MUEANG NAKHON RATCHASIMA DISTRICT, NAKHON RATCHASIMA PROVINCE - Lorpattanakasem, Waranya; Phatisena, Tanida (Primary Health Care Journal (Northeastern Edition), 2023)
This cross-sectional analytical study to determine the association between health literacy and preventing and controlling behavior for covid-19 prevention and control among village health volunteers. The sample size consisted of 354 people who were village health volunteers in Mueang Nakhon Ratchasima district, Nakhon Ratchasima province. The research tool was a questionnaire, data were analyzed by statistical distribution of frequency, percentage, mean, and standard deviation, minimum and maximum values, Pearson product-moment correlation coefficients and stepwise multiple regression analysis, significance was at .05 level. The results of the study showed that the factors that association between health literacy with the prevention and control behavior for Covid-19 among village health volunteers were cognitive skill, self-management skill, media literacy skill, decision skill, access skill and communication skill statistically significant (r = .760, .756, .735, .714, .670 and .420, p-value < .05). Factors that can collectively predict behavior in prevention and control behavior for Covid-19 include cognitive skill, self-management skill, media literacy skill and access skill, and can explain variations in the prevention and control behavior for Covid-19 was at 72.4 percent (R2 = .724, R2adj = .721, B = 11.324, Std. E = .629) Statistically significant was at .05 level.